2020
DOI: 10.3390/ijms21030921
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy-Associated MADS-Box (DAM) Genes Influence Chilling Requirement of Sweet Cherries and Co-Regulate Flower Development with SOC1 Gene

Abstract: Floral bud dormancy release of fruit tree species is greatly influenced by climate change. The lack of chilling accumulation often results in the occurrence of abnormal flower and low yields of sweet cherries (Prunus avium L.) in warm regions. To investigate the regulation of dormancy in sweet cherries, six DAM genes with homology to peach DAM, designated PavDAM1-6, have been identified and characterized. Phylogenetic analysis indicate that these genes are similar to DAMs in peach, apple and pear. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 49 publications
(73 reference statements)
7
44
0
Order By: Relevance
“…Recently, similar interactions between PavDAM1/5 and the dormany-associated SUPPRESSOR OF OVEREXPRESSION OF CO1 PavSOC1 were reported by Wang, et al 118 in sweet cherry. The authors suggested these interactions between DAMs and SOCs could play a role in bud dormancy regulantion.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, similar interactions between PavDAM1/5 and the dormany-associated SUPPRESSOR OF OVEREXPRESSION OF CO1 PavSOC1 were reported by Wang, et al 118 in sweet cherry. The authors suggested these interactions between DAMs and SOCs could play a role in bud dormancy regulantion.…”
Section: Discussionsupporting
confidence: 75%
“…DAM genes have been reported to be the major regulatory factors involved in the control of dormancy induction and release in flower bud of relative species 61,118,119 . Blast analyses against the genome of 'Sanyueli' plum enabled us to identify six PsDAM genes, including PsDAM1 (PsSY0028611), PsDAM2…”
Section: Dormancy Associated Mads-box (Dam) Genes In Plum Genomementioning
confidence: 99%
“…A large number of coordinating key genes that regulate signaling pathways were identified. For example, DOR-MANCY ASSOCIATED MADS-BOX (DAM) and the flowering genes FLOWERING TIME (FT), CENTRORA-DIALIS 1 (CENL1), and SOC1 (SUPPRESSOR OF OVER-EXPRESSION OF CO1) have been suggested to regulate endodormancy [29][30][31][32][33]. During both the induction and release of endodormancy, the DAMs expression profile indicated the possible existence of dose-dependent inhibitors of bud burst [14,34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, yeast two hybrid analysis confirmed the presence of three common protein interactors between PpeDAM6 and SVP: FUL (Balanza et al, 2014), SEP2 (Trigg et al, 2017) and SOC1 (de Folter et al, 2005). In addition, SOC1-like have been also shown to interact with DAM6 from apricot (Kitamura et al, 2016) and sweet cherry (Wang et al, 2020a), similarly to the interaction observed between SVP-like and SOC1-like in kiwifruit (Wu et al, 2017). SOC1…”
Section: Potential Role Of Ppedam6 In the Flowering Pathwaymentioning
confidence: 68%
“…27), resembling 35S::AtSVP plants in the literature, with the exception of the late flowering phenotype. Likewise, the overexpression in Arabidopsis of PavDAM1-6 and SVP-like genes, which are involved in the dormancy process in Prunus avium and Actinidae deliciosa respectively, resulted in similar defects in the flower phenotypes (Wang et al, 2020a;Wu et al, 2012).…”
Section: Potential Role Of Ppedam6 In the Flowering Pathwaymentioning
confidence: 96%